2010
DOI: 10.3136/fstr.17.55
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Eleven Flavor Precursors, S-Alk(en)yl-L-Cysteine Derivatives, in Seven Allium Vegetables

Abstract: Using high-performance liquid chromatography, 11 sulfur-containing flavor precursors were determined quantitatively in seven Allium vegetables: garlic (Allium sativum), onion (A. cepa), Welsh onion (A. fistulosum), Chinese chive (A. tuberosum Rotter), rakkyo (A. chinense G. Don), 'asatsuki' (A. schoenoprasum), and leek (A. porrum). Keywords: alliin, Alliums, flavor precursor, glutamyl peptide, high-performance liquid chromatography, isoalliin, S-alk(en) yl-L-cysteine *To whom correspondence should be addressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 26 publications
1
31
2
Order By: Relevance
“…This conclusion is supported by a previous report using synthetic thiosulfinates (Kubec et al, 2004). These results indicate that the main causal agents involved originally in garlic bulbs are alliin, isoalliin and alliinase (Yamazaki et al, 2011).…”
Section: Resultssupporting
confidence: 81%
“…This conclusion is supported by a previous report using synthetic thiosulfinates (Kubec et al, 2004). These results indicate that the main causal agents involved originally in garlic bulbs are alliin, isoalliin and alliinase (Yamazaki et al, 2011).…”
Section: Resultssupporting
confidence: 81%
“…Sturon, although other authors reported a prevalence of isoalliin (Yamazaki et al 2010;Bernaert et al 2012). Starkenmann et al (2011) found a much higher level of isoalliin than alliin in onion tissues.…”
Section: Resultsmentioning
confidence: 75%
“…Food Sci., 34, 2016(2): 127-132 doi: 10.17221/268/2015 between numerous onion cultivars. It has also been reported that the content of secondary metabolites in Allium species changes after harvest (Yamazaki et al 2010;Bernaert et al 2013). Such information is important for consumers.…”
mentioning
confidence: 99%
“…The freeze-dried samples were powdered using a food blender and stored at −20℃ until analysis. The sample powders were evaluated according to procedures previously described (Yamazaki et al, 2011). Briefly, the sample powders (500 mg) were extracted with 25 mL of methanol-water-formic acid (50:50:1, v/v/v).…”
Section: Hplc Analysis Of S-alk(en)yl-l-cysteines In Stored Garlic Samentioning
confidence: 99%
“…Recently, it was reported that S-(2-propenyl)-L-cysteine sulfoxide (alliin) is also a discoloration factor (Kubec et al, 2004;Imai et al, 2006a). In contrast to alliin, isoalliin is usually abundant in onion but scarce in garlic (Yamazaki et al, 2011). Reportedly, the alliinase (EC 4.4.1.4) product of isoalliin, presumed to be 1-propenyl 1-propenethiosulfinate, reacts with amino acids to produce pigment precursors.…”
Section: Introductionmentioning
confidence: 99%